2018
DOI: 10.1080/07373937.2018.1473418
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration of potato slices following brief dipping in osmotic solutions: Effect of conditions and understanding the mechanism of water loss

Abstract: A novel variant of osmotic dehydration, named here as post-dipping dehydrationwhere a material is dipped in a salt or sugar solution for a very short time followed by simple exposure to ambient conditions was explored with the aim of lowering water content of potato slices but at the same time not gain a high level of sugar/salt. The rate of water loss, which was rapid initially, was found to approach equilibrium. This paper also explored whether the water loss process could subsequently be kick started once a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…The gradual increase in WL can be observed for all process conditions when immersion time is increased during the OD process. Rapid water removal was reported on various agricultural products for the first 2 hrs of processing time due to a high osmotic driving force between the sample and the hypertonic solution (31)(32)(33). From the graph, it is apparent that the WL increased for all coating conditions when compared to the uncoated sample.…”
Section: Water Loss (Wl)mentioning
confidence: 99%
“…The gradual increase in WL can be observed for all process conditions when immersion time is increased during the OD process. Rapid water removal was reported on various agricultural products for the first 2 hrs of processing time due to a high osmotic driving force between the sample and the hypertonic solution (31)(32)(33). From the graph, it is apparent that the WL increased for all coating conditions when compared to the uncoated sample.…”
Section: Water Loss (Wl)mentioning
confidence: 99%
“…The relationship between water loss and solute gain is a good indicator of the dehydration efficiency during osmotic dehydration process (Mokhtar, Ghawi, & Niranjan, ; Ramallo & Mascheroni, ). Dehydration efficiency values decreased with the number of syrup reuse cycle in one‐stage treatments and remained almost unchanged in multi‐stage treatments (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The selection of hypertonic solution relies on the expected water loss and solid gain, and also on the desired nutritional and sensory properties of the final food product. Concentrated sucrose solution, sodium chloride solutions and their combinations are usually used as hypertonic solutions [15,16]. Recent examinations reported that sugar beet molasses is a very powerful osmotic medium for dehydration of fruits, vegetables and meat.…”
Section: Introductionmentioning
confidence: 99%